Measurement of ki using ionization chamber and gafchromic films for mobile x-ray machine - Nasir, Nurul Aishah Mohd (Universiti Sains Malaysia, 2016)
The aim of this study is to determine the incident air kerma (Ki) for mobile unit x-ray by using ionization chamber and Gafchromic films based on TRS457. Examination of abdomen and chest had been chosen in this study. Exposure parameters that had been used was 83kVp/ 12.5 mAs, 85kVp/32.0 mAs and 85kVp/ 40mAs for abdomen examination, while for chest was 120kVp/ 5mAs, 125kVp/1.0 mAs and 125kVp/1.6mAs. The first objective was to study the dose response of the Gafchromic XR-QA2 and XR-RV3 films. The films irradiated with 70, 80, 90 and lOOkVp for 20mAs. The films were scanned by using Epson 10000XL flatbed scanner after 24hours irradiation, to obtain the pixel value of the films. Then, the pixel value had to be changed to optical density to plot the linearly dose response graph. The study showed linear relationship for Gafchromic XR-QA2 film, but not for XR-RV3 films since the Gafchromic XR-RV3 films was fluoroscopic-guided favour. The study was preceded by obtaining of calibration curve for Gafchromic XR-QA2 films to get the dose from the films. The cross-checked dose obtained from IC and calibration curve used for the calculation for measurement of Ki. The result showed Ki for films was higher than IC due to the difference of sensitivity. Large variation was displayed in term of percentage difference (%) for abdomen was 34% to 108%, while for chest was 32% to 350%. The reasons why the large variation of percentage difference were due to the usage of parameter that contributed to out of range dose, properties of films and mishandling of the films. As a conclusion, the variation of percentage difference is not significantly different between IC and Gafchromic films if the dose in range applied in this study.